Enhancing hydroponic leaf lettuce (Lactuca sativa) production through optimized nutrient formulations - MARK AL-JAMIE J. MUTTULANI (Asian Journal of Agriculture, 2025)
Abstract. Muttulani MAJ. 2025. Enhancing hydroponic leaf lettuce (Lactuca sativa) production through optimized nutrient formulations. Asian J Agric 9: 415-422. In leaf lettuce production, optimizing nutrient formulations within a hydroponic production system is crucial for enhancing yield, reducing environmental impact, increasing water efficiency, and maintaining a balanced nutrient supply. Despite substantial research, ideal nutrient formulations for lettuce hydroponic production remain insufficiently explored. A well-formulated nutrient solution provides plants with the necessary macro and micro nutrients for healthy growth and development. Thus, this research investigated five nutrient formulations using calcium nitrate, magnesium sulfate, and water-soluble fertilizer on lettuce's growth and yield performance under a hydroponic production system, arranged in a completely randomized design with five replicates. Results revealed that Formulation 3-110 g (NPK) + 70 g MgSO4/ 500 mL H20 (Solution 1) + 180 g Ca(NO3)2/500 mL H20 (Solution 2) significantly improved percentage survival (98%), leaf-sized in terms of its width (16.61 cm) and length (23.64 cm), number of leaves (4.14), heaviest weight of the crown (332.63 g), the longest length of roots (37.20 cm), and highest rooting percentage (98%). The study's findings highlight the significant influence of the aforementioned nutrient formulation on the hydroponic production of lettuce, affecting its quality and yielding an increase of about 60-80%. The study provides a comprehensive insight into optimizing nutrient formulations for loose leaf lettuce production, which can be adapted to other types of lettuce, empowering farmers to significantly increase crop yield, improve food security, increase profitability, and promote sustainable agriculture.